Enhanced electrical performance for heterojunction with intrinsic thin-layer solar cells based photovoltaic thermal system with aluminum collector. (July 2020) - Pang, Wei; Cui, Yanan; Zhang, Qian; Yan, Hui
Abstract: Crystalline silicon heterojunction with intrinsic thin-layer photovoltaic (HIT-PV) module produces more output power, compared with the c-Si photovoltaic module. However, it presents a risk of overheating in hot weather. In this paper, we used a new cooling design of the heterojunction with intrinsic thin-layer photovoltaic thermal (HIT-PVT) module to lower the temperature using laminated encapsulation of an aluminum collector in outdoor climates. The measured electrical, thermal and total efficiencies of a HIT-PVT system can catch up to 17.47%, 34.71% and 52.18%, respectively. Moreover, comparing with HIT-PV module, the output power of the HIT-PVT module was enhanced by 5.58% with coolant circulation, and the converted electrical energy can be increased by 9.81% with the designed HIT-PVT module. In addition, the primary energy savings of the new HIT-PVT and HIT-PV systems were 79.77% and 43.71%, respectively.